The Role of Distinctive Capabilities in the Relationship between Work Ethics and Marketing Citizenship: An Empirical Study on Banking Sector in Al-Jouf Region - Abo Lifa, Sanaa; Aloqool, Abdalrazzaq (The Arab Journal of Administration, 2021)
The study aimed to identify the role of distinctive capabilities in the relationship between the dimensions of work ethics and the dimensions of marketing citizenship. The study used the descriptive analytical method, and was applied on a sample consists of (170) employees working in banking sector in Al-Jouf region, K.S.A. Study’s hypotheses were developed, then tested by using statistical analyses via the Statistical Package for Social Sciences SPSS version (25), and AMOS version (26). The study found that the degree of awareness of individuals about the dimensions of work ethics, dimensions of distinctive capabilities, and dimensions of marketing citizenship are above average. The study also found that there is an indirect and significant impact on some dimensions of work ethics (utilitarian approach, moral – rights approach, commitment approach, and traits approach) on the dimensions of marketing citizenship (legal responsibility, ethical responsibility, and philanthropic responsibility) through the interventional intermediate variable –distinctive capabilities- (individuals, marketing and public and governmental relations). The study suggests that the banks should encourage ethical leadership within the bank, examine decisions taken within the bank from its ethical aspect, prepare training programs for employees to educate them about the marketing citizenship strategy, and support the community that operate in it.